Effectiveness of argument-driven inquiry (ADI) on students’ concept mastery and argumentation skills in reproductive system - Medisa Shania Divena; Yanti Hamdiyati; Any Aryani (Biosfer: Jurnal Pendidikan Biologi, 2021)
This study aims to determine the effect of the Argument-Driven Inquiry (ADI) learning model application on the concepts mastery and argumentation skills of high school students on reproductive system material. The research method used quasi-experimental and non-equivalent control group design. The sample of this research were second-grade high school MIPA students in one of the public high schools in Bandung, which consists of 30 students in the experimental class and 33 students in the control class. The sample was taken by using the purposive sampling technique. The instruments used consisted of a concept mastery test in the form of multiple choices, an argumentation ability test in the form of an essay, and questionnaire of students’ responses to the ADI model. The results showed that the application of the ADI learning model significantly affected the students' concepts mastery on reproductive system material in the experimental class compared to the control class, especially in the cognitive aspects of C3 (applying). The results also show that the application of the ADI learning model significantly affects the ability of argumentation, especially on the warrant component. Student response data shows that students respond very well to the application of the ADI learning model. Therefore, the ADI learning model is recommended for biology teachers to improve students’ concepts mastery mastery and argumentation skills in other biological materials.